Forensic science handbook. Volume I - Saferstein, Richard, 1941-; Hall, Adam B. (Boca Raton, FL : CRC Press, 2020)
Originally published in 1982 by Pearson/Prentice-Hall, the Forensic Science Handbook, Third Edition has been fully updated and revised to include the latest developments in scientific testing, analysis, and interpretation of forensic evidence. World-renowned forensic scientist, author, and educator Dr. Richard Saferstein once again brings together a contributor list that is a veritable Who's Who of the top forensic scientists in the field. This Third Edition, he is joined by co-editor Dr. Adam Hall, a forensic scientist and Assistant Professor within the Biomedical Forensic Sciences Program at Boston University School of Medicine. This two-volume series focuses on the legal, evidentiary, biological, and chemical aspects of forensic science practice. The topics covered in this new edition of Volume I include a broad range of subjects including: Legal aspects of forensic science Analytical instrumentation to include: microspectrophotometry, infrared Spectroscopy, gas chromatography, liquid chromatography, capillary electrophoresis, and mass spectrometry Trace evidence characterization of hairs, dust, paints and inks Identification of body fluids and human DNA This is an update of a classic reference series and will serve as a must-have desk reference for forensic science practitioners. It will likewise be a welcome resource for professors teaching advanced forensic science techniques and methodologies at universities world-wide, particularly at the graduate level.
"Originally published in 1982 by Pearson/Prentice-Hall, the Forensic Science Handbooks, Third Edition has been fully updated and revised to include the latest developments in scientific testing, analysis, and interpretation of forensic evidence. World-renowned forensic scientist, author, and educator Dr. Richard Saferstein once again brings together a contributor list that is a veritable Who's Who of the top practicing forensic scientists in the field. This Third Edition, he is joined by the Director of the Core Mass Spectrometry Facility at the Barnett Institute of Chemical and Biological Analysis at Northeastern University, co-editor Dr. Adam Hall. The two volumes focus on the analytical, biological, and chemical aspects of forensic science practice, and the topics covered in this new edition of Volume I include a broad range of subjects including: Legal Aspects of Forensic ScienceAnalytical Instrumentation such as Microscopy, Microspectrophotometry, IR Spectroscopy, GC, LC, CE and MSTrace Evidence Characterization of hairs, dust and inksBiological Identification of body fluids and human DNAThis is an update of a classic reference and will serve as a must-have desk reference for forensic science practitioners. It will likewise be a welcome resource for professors teaching advanced forensic science techniques and methodologies at universities world-wide, particularly at the graduate level."--Provided by publisher
OCLC-licensed vendor bibliographic record.
Keywords: Criminal investigation -- United States -- Handbooks, manuals, etc; Crime scene searches -- United States -- Handbooks, manuals, etc; Forensic sciences -- United States -- Handbooks, manuals, etc; Chemistry, Forensic -- United States -- Handbooks, manuals, etc; Evidence, Criminal -- United States -- Handbooks, manuals, etc; SCIENCE -- Chemistry -- General; SCIENCE -- Chemistry -- Analytic; LAW -- Forensic Science; SCIENCE -- Chemistry -- General; SCIENCE -- Chemistry -- Analytic